Measurement of the energy asymmetry in $$t{\bar{t}}j$$ tt¯j production at $$13\,$$ 13 TeV with the ATLAS experiment and interpretation in the SMEFT framework. - Beauchemin, P. H.; Croft, V..; Drobac, A. S.; Kaya, F. I.; Sliwa, K..; Son, H.. (Tufts University. Tisch Library., 2022)
Springer Open.